Head & Face Medicine - Meyer, Ulrich; Wiesmann, Hans Peter; Stamm, Thomas
Head & Face Medicine is a multidisciplinary open access journal that publishes basic and clinical research concerning all aspects of cranial, facial and oral conditions. The journal covers all aspects of cranial, facial and oral diseases and their management. It has been designed as a multidisciplinary journal for clinicians and researchers involved in the diagnostic and therapeutic aspects of diseases which affect the human head and face. The journal is wide-ranging, covering the development, aetiology, epidemiology and therapy of head and face diseases to the basic science that underlies these diseases. Management of head and face diseases includes all aspects of surgical and non-surgical treatments including psychopharmacological therapies. To date, no journal has provided readers with multidisciplinary information in the field of head and face medicine. With this expanding field covering surgical and non-surgical management of diseases and including original research concerning basic science, development, aetiology, and epidemiology of diseases in the complex cranial and facial area, information for a broad readership is needed. Head & Face Medicine provides an open access journal that will cover this interdisciplinary area.